Mamilov N.Sh., Amirbekova F.T., Khabibullin F.Kh., Adilbaev Zh.A., Bekkozhaeva D.K., Kozhabaeva E.B. New data on morphometry and biology of alien snakehead Channa argus in the Syrdarya River: Al-Farabi Kazakh National University, Scientifc Research Institute of Biology and Biotechnology problems - Mamilov N.Sh., Amirbekova F.T., Mamilov N.Sh., Amirbekova F.T., (Eurasian Journal of Ecology, 2018)
The Amur (or northern) snakehead, Channa argus (Cantor, 1842), was unintentionally introduced in the Aral basin in 1961-1963. This fish species now distributed worldwide and is considered as a dangerous invader. Furthermore number and abundance of alien fish species is considered as an index of unfavorable state of water ecosystems. Therefore, the investigation of morphological and biological variability in space and time should reveal ecological plasticity of the population of Amur snakehead in the Syrdarya River. Fishes for the examination were caught using standard fishing tackles. Physical and chemical water characteristics were assessed by the most common methods. Turbidity of the water, salinity, temperature and pH, color and odor of the water were determined. The population of snakehead was presented by adult and young fishes. Growth rate was slowly than in the first time of naturalization. Comparative analysis of morphological features did reveal neither significant shifts nor reduction of variability of the population in the Syrdarya River. Adult fishes cared their young fishes longer that it was supposed before. Grow rate of the fishes was slowly than in the first time after introduction. Minimal body length of mature fishes was about 280 mm. Amur snakehead is trophic competitor with indigenous piscivorous fish species. Now the Amur snakehead is a regular member of fish community in the Syrdarya River. Key words: Channa argus, Amur snakehead, Syrdarya River, morphology, biology